2014
DOI: 10.5505/sakaryamj.2014.29863
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of Neutrophil Lymphocyte ratio in acute appendicitis

Abstract: Amaç: Çalışmamızın amacı akut apandisitte nötrofil lenfosit oranının (NLR) tanısal dağerini değerlendirmektir. Gereç ve Yöntemler: Apendektomi uygulanan 310 hasta çalışmamıza dahil edildi.Hastaların yaşları, cinsiyetleri, preoperatif beyaz küre, nötrofil yüzdesi, lenfosit yüzdesi ve NLR'leri, çekilmiş olan ultrasonografi (USG) ve patoloji sonuçları retrospektif olarak elde edildi. İstatistik analizde student t test, ki-kare testi ve olasılık oranları kullanıldı. Bulgular: Çalışmamıza appendektomi ameliyatı yap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
3
6
1
Order By: Relevance
“…Significantly higher NLR level in adult patients with positive appendectomy compared to patients with negative appendectomy is also supported by the findings of Kahramanca et al [12]. The statistically significantly lower NLR values in Group 1, observed in our and in previous studies, suggest that NLR value may be helpful in differentiating non-operated vs. operated patients with AA [9,12,22].…”
Section: Or -Odds Ratio CI -Confidence Interval Wbc -White Blood Cesupporting
confidence: 84%
See 1 more Smart Citation
“…Significantly higher NLR level in adult patients with positive appendectomy compared to patients with negative appendectomy is also supported by the findings of Kahramanca et al [12]. The statistically significantly lower NLR values in Group 1, observed in our and in previous studies, suggest that NLR value may be helpful in differentiating non-operated vs. operated patients with AA [9,12,22].…”
Section: Or -Odds Ratio CI -Confidence Interval Wbc -White Blood Cesupporting
confidence: 84%
“…Our results are in the accordance with the results of Yazici et al [9], who found in children statistically significant differences in NLR values between appendicitis patients who were treated operatively compared with patients with non-specific abdominal pain. Sevim et al [22] also observed significantly higher NLR levels in adult patients with AA compared to patients without AA. Significantly higher NLR level in adult patients with positive appendectomy compared to patients with negative appendectomy is also supported by the findings of Kahramanca et al [12].…”
Section: Or -Odds Ratio CI -Confidence Interval Wbc -White Blood Cementioning
confidence: 87%
“…There are several studies in the literature using NLR as a marker in certain acute abdominal events, including mesenteric ischemia, peptic ulcer perforation, and acute cholecystitis, as a marker of lymph node metastasis in certain types of cancer and investigating its value in vascular events, such as aorta dissection and acute coronary syndrome, in rheumatic diseases, such as rheumatoid arthritis and ankylosing spondylitis, in the exacerbation of chronic obstructive lung disease, after acute tonsillitis and several infections such as deep neck infection. [5][6][7][8][9][10] In our study, we found no significant difference between the groups concerning the NLR values (for survivors: 14.82±23.39; for non-survivors: 15.13±15.56) (p=0.338).…”
Section: Discussioncontrasting
confidence: 60%
“…De jager et al showed the presence of lymphocytopenia in their study, and concluded that NLR was able to predict bacteriemia with a higher rate 7 . Sevim et al evaluated patients with acute appendicitis, and showed a statistically significant relationship between NLR and complication rate 8 . NLR increases in inflammatory conditions.…”
mentioning
confidence: 99%